Madagascine Induces Vasodilatation via Activation of AMPK - Chen, Dapeng; Lv, Bochao; Kobayashi, Sei; Xiong, Yongjian; Sun, Pengyuan; Lin, Yuan; Genovese, Salvatore; Epifano, Francesco; Hou, Shanshan; Tang, Fusheng; Ji, Yunyan; Yu, Dandan (Frontiers in Pharmacology, 2016)
Madagascine (3-isopentenyloxyemodin) can be chemically synthesized or purified from several Rhamnus species, and it is found to have more potent biological activities than the parent compound emodin. The aim of this study is to characterize the vasodilatory effect of madagascine on vasoconstriction and sphingosylphosphorylcholine induced vasospasm in ex vivo and reveal the potential mechanisms in vitro. The effects of madagascine on vasoconstriction of rat mesenteric resistance arteries (MRAs) induced by K+, methoxamine, and endothelin-1 were respectively studied. The cholesterol-enriched porcine coronary vascular smooth muscle (VSM) strips were used to investigate the effects of madagascine on abnormal constriction induced by sphingosylphosphorylcholine (SPC) which has a pivotal role in vasospasm. The vasodilatory effect was induced by madagascine (0.3-100μM) in isolated rat MRAs and the vasodilatory effect was blocked by NO synthase inhibitor L-NAME and AMPK inhibitor compound C. Madagascine (10 μM) also significantly relaxed the abnormal constriction in porcine VSM induced by SPC and the effect was abolished by compound C. Madagascine significantly increased the phosphorylation of endothelial nitric oxide synthase (eNOS) in endothelial cells while decreasing the phosphorylation of myosin phosphatase target subunit 1 (MYPT1) in VSM cells. Madagascine-induced vasodilatation was abrogated using small interfering RNA knockdown of AMPK. In summary, madagascine exerted vasodilatation through activating AMPK, leading to the activation of eNOS in endothelium and inhibition of ROCK/MYPT1 in VSM. This study suggests the potential value of madagascine in amelioration of vasospasm related cardiovascular diseases.